2005
DOI: 10.1016/j.vacuum.2005.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Determination of atomic depth profile in ion-beam mixed bilayer systems from the Rutherford backscattering data

Abstract: Ion-beam irradiation has been extensively used to induce mixed layers and phases formation in the metal-metal and metal-silicon systems. Rutherford backscattering spectrometry (RBS) is currently used to investigate the mixed layers. In such studies, it is important to know the depth profile of each atomic species of the mixed layer. For this purpose, a simple method for the determination of the atomic fraction of each element at a given depth of the mixed layer is described. This method does not need a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…On the contrary of Au and Ni signals spreading towards Si side, Ar peak at a fluence of 5×10 16 ions/cm 2 shows symmetry around its maximum position implying Gaussian type distribution commonly observed in case of implanted ions in solids at quite low fluences. Moreover, the allocation of Au, Ni and Si atoms corresponding to different depths within the as-deposited and irradiated samples has been calculated using the backscattering data with the help of a direct analytical method [196].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary of Au and Ni signals spreading towards Si side, Ar peak at a fluence of 5×10 16 ions/cm 2 shows symmetry around its maximum position implying Gaussian type distribution commonly observed in case of implanted ions in solids at quite low fluences. Moreover, the allocation of Au, Ni and Si atoms corresponding to different depths within the as-deposited and irradiated samples has been calculated using the backscattering data with the help of a direct analytical method [196].…”
Section: Applicationsmentioning
confidence: 99%
“…In another study total mixing has been reported at Au/Si thin film interfaces with Ar ion irradiation. The depth profiles using a computer program [196] reveal two distinct regions. At the surface, a mixed layer with homogeneous concentrations of Au and Si atoms is observed which is of the approximate composition of Au 70 Si 30 .…”
Section: Au-simentioning
confidence: 99%
“…These observations well agree with Holloway and Sinclair [12] in case of Ti-Si thin films. The broaden of peaks in case of Au/Si bilayer structure observed by authors [13] with ion influence.…”
Section: Rutherford Back Scattering Spectrometrymentioning
confidence: 65%
“…[17,18]. The method is particularly suitable for this system as the peaks corresponding to different elements are separated and well resolved.…”
Section: Resultsmentioning
confidence: 99%
“…RBS data of as deposited and ion irradiated samples play the main role in this study and to analyze the data, an efficient analytical method mentioned in Refs. [17,18] has been used. Using that method, depth profiles of different components of co-sputtered and ion irradiated Au-Ni thin films on Si has been investigated.…”
Section: Resultsmentioning
confidence: 99%